Sex-specific risk signals and onset patterns of drug-induced peripheral neuralgia: a 20-year pharmacovigilance analysis based on FAERS real-world dat - Wang, Xianyan; Deng, Min; Liao, Wanjun; Quan, Yiwen; Xu, Xiaoxue (Frontiers in Pharmacology, 2025)
BackgroundPeripheral neuralgia is a chronic pain syndrome resulting from peripheral nerve damage and has been increasingly linked to certain drugs, leading to drug-induced peripheral neuropathy (DIPN). While the neurotoxic potential of many drugs has been recognized, the gender-specific patterns of DIPN remain insufficiently studied.ObjectiveTo identify potential drug safety signals associated with DIPN and explore gender-based differences in risk using real-world pharmacovigilance data.MethodsThis retrospective pharmacovigilance study utilized the FDA Adverse Event Reporting System (FAERS) database from 2004 to 2024. Disproportionality analysis (DPA), specifically Reporting Odds Ratio (ROR), was applied to detect associations between drugs and DIPN. Drug and adverse event terms were standardized using RxNorm and MedDRA dictionaries. Weibull distribution modeling was employed to analyze time-to-onset (TTO) characteristics of high-risk drugs in male and female populations.ResultsA total of 21,609 adverse event reports of DIPN were analyzed, showing a continuous increase in reporting over two decades. Seventy-two drugs were identified as having potential DIPN risk signals, with 25 drugs showing strong associations after statistical adjustments. Among them, adalimumab, ciprofloxacin, and lenalidomide had the highest number of reports. Eighteen drugs presented new risk signals not previously mentioned in official drug labeling. Gender-specific analysis revealed 49 risk drugs in females, 32 in males, with 23 drugs overlapping. Time-to-onset analysis showed most adverse events occurred early in treatment, as indicated by Weibull shape parameters (β < 1) for all major drugs.ConclusionThis study revealed novel and sex-specific DIPN risk signals using large-scale real-world data. It highlights the importance of early monitoring of neurotoxic effects during drug treatment and provides strong support for implementing gender-sensitive pharmacovigilance strategies and individualized medication risk management.